Artur, Gauvain e Keu : representações da realeza em Chrétien de Troyes - Laranjinha, Ana Sofia (1996)
At the Arthurian court of Chrétien de Troyes Gauvain and Keu both play a central role: together with King Arthur they constitute a composite royal character, in which the knights represent the opposite and complementary principles of the solar world and the ctonic world, with the king, at its centre, harmonising the opposites and representing the axis of alteration between the two principles. The comparison of this triad with the Gaulish triad of Cernunnos, Apollo and Mercury allows us a better understanding of the functions of the three characters and helps to explain the insufficiencies of Gauvain and of Arthurian royalty in the final romance of Chretien de Troyes.